1956
DOI: 10.1021/ac60116a020
|View full text |Cite
|
Sign up to set email alerts
|

Titration of Mercury with Bis(2-hydroxyethyl)dithiocarbamate

Abstract: A direct titrimetric method permits the determination of mercury (II) in the presence of chloride, bromide, and numerous metal ions. The mercury is titrated with a standard dithiocarbamate solution in the presence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1957
1957
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
(4 reference statements)
3
18
0
Order By: Relevance
“…Reagents. Ammonium bis(2-hydroxyethyl)dithiocarbamate was prepared by a modification of the procedure described by Fritz and Sutton (24). Dissolve 10.5 (0.10 mol) of diethanolamine in 50 mL of methanol.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents. Ammonium bis(2-hydroxyethyl)dithiocarbamate was prepared by a modification of the procedure described by Fritz and Sutton (24). Dissolve 10.5 (0.10 mol) of diethanolamine in 50 mL of methanol.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of EDTA concentration, Hg 2+ was masked, and the response to organic mercury was effectively enhanced. It was supposed that the EDTA assisted the competition reaction between organic mercury and CuDDTC 2 complex, 30 as indicated by the The colorimetric response time of the CuDDTC 2 −Au NPbased probe to organic mercury was first investigated prior to the sensitivity study. As shown in Figure S3B (Supporting Information), the equilibrium was achieved in 2 min, and thus 2 min was selected as the reaction time in the following tests for organic mercury.…”
Section: Scheme 1 Schematic Illustrations Of (A) Au Np-based Colorimmentioning
confidence: 99%
“…A review of the dithiocarbamate literature showed that bis(2-hydroxyethyl)dithiocarbamate (HEDC) has been used as a colorimetric reagent to form a water-soluble, intensly colored complex with copper(II) (14,15). HEDC has also been used as a titrant in the determination of mercury(II) (16) and as a colorimetric reagent in the determination of molybdenum (VI), uranium(VI) (17), and nickel(II) (18). The sodium salt of HEDC (designated NaHEDC) was selected as the most promising reagent for this study.…”
mentioning
confidence: 99%